2002
DOI: 10.1109/tse.2002.1000452
|View full text |Cite
|
Sign up to set email alerts
|

The optimal class size for object-oriented software

Abstract: A growing body of literature suggests that there is an optimal size for software components. This means that components that are too small or too big will have a higher defect content (i.e., there is a U-shaped curve relating defect content to size). The U-shaped curve has become known as the "Goldilocks Conjecture". Recently, a cognitive theory has been proposed to explain this phenomenon, and it has been expanded to characterize object-oriented software. This conjecture has wide implications for software eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 41 publications
1
46
0
2
Order By: Relevance
“…In the case of a LR model, a threshold can be defined as [119]: A recent study [33] has shown that there are no size thresholds for object-oriented systems. Therefore size can be kept as a continuous variable in the model.…”
Section: Specifying Thresholdsmentioning
confidence: 99%
“…In the case of a LR model, a threshold can be defined as [119]: A recent study [33] has shown that there are no size thresholds for object-oriented systems. Therefore size can be kept as a continuous variable in the model.…”
Section: Specifying Thresholdsmentioning
confidence: 99%
“…The first study demonstrated that an absence of size thresholds for object-oriented classes (El-Emam, Benlarbi, Goel, Melo et al, 2000). The remaining two studies demonstrated that an absence of threshold effects for a subset of the metrics described earlier Glasberg et al, 2000).…”
Section: Thresholdsmentioning
confidence: 78%
“…A recent series of studies led by the author investigated thresholds for objectoriented metrics El-Emam, Benlarbi, Goel, Melo et al, 2000;Glasberg et al, 2000). The first study demonstrated that an absence of size thresholds for object-oriented classes (El-Emam, Benlarbi, Goel, Melo et al, 2000).…”
Section: Thresholdsmentioning
confidence: 99%
“…This intruder process will be assisted by concerned entities and supporting services [19] [22]. The measurements about the various entities and their behaviour can be obtained through design constructs such as coupling, cohesion, encapsulation and polymorphism [12] [13]. The software security team through this model based on coupling metrics can quantify the confidentiality for the system under development so as to improve its overall security [7] [8] [9].…”
Section: Model For Quantification Of Effects Of Coupling Metrics On Cmentioning
confidence: 99%